Analysis of lncRNA in the skeletal muscle of rabbits at different developmental stages - Zhu, Cuiyun Y.; Zheng, Qi; Pan, Qianqian Q.; Jing, Jing; Qin, Shuaiqi Q.; Lou, Mengyu Y.; Yang, Yuhang H.; Wei, Jinbo B.; Li, Shuang; Fang, Fugui G.; Liu, Yong; Ling, Yinghui H. (Frontiers in Veterinary Science, 2022)
It is universally acknowledged that lncRNA plays an important role in the regulation of animal skeletal muscle development regulation However, there is a lack of relevant research on lncRNA in rabbit skeletal muscle development. Thus, we explored the expression profiles of lncRNA in rabbits at three growth stages (2-week-old fetus, 6-week-old kitten and 6-month-old adult) using RNA-seq. A total of 554 differentially expressed lncRNAs (235 up- and 319 down-regulated) were found between the kitten and fetus groups and 19 (7 up- and 12 down-regulated) between the kitten and adult groups and 429 (115 up- and 314 down-regulated) between the fetus and adult. The enrichment pathways in the kitten and fetus groups were mainly concentrated at AMPK and PI3K-Akt signaling pathways, and the co-expression results revealed that LINC-2903, LINC-2374, LINC-8591 plays a role in early maintenance of skeletal muscle development. The enriched pathways in the fetus and adult groups were mainly involved in PI3K-Akt signaling pathways with a strong association found in mTOR signaling pathways. Analysis of the co-expression results suggests that LINC-5617 may be involved in the proliferation of embryonic skeletal muscle cells, and that LINC-8613 and LINC-8705 may provide energy for postnatal skeletal muscle development. The specific roles of different lncRNAs in different developmental stages of New Zealand White rabbits obtained. This will contribute to the subsequent study on the regulatory mechanism of muscle development in New Zealand White rabbits.